Perlindungan Saksi Perkara Tata Usaha Negara Dalam Perspektif Keadilan Pancasila - Mansyah, Muh Sutri; Karim, La Ode Muhammad; Ali, La Ode Bunga; Gurusi, La; Nurcahyo, Edy (Kertha Patrika, 2024)
Witnesses are one of the means of evidence that can be used in administrative court cases. However, over time, there have been instances where witnesses face threats. Arising from this issue, the researcher is interested in studying and analyzing how witness protection in administrative court cases is addressed from the perspective of Pancasila justice. This study employs doctrinal legal research. The findings show that witness protection in administrative court cases is not yet regulated in Indonesia. Based on an analysis of the Witness and Victim Protection Law (UU PSK), it only provides protection for witnesses in criminal cases. Meanwhile, the Administrative Court Law (UU Peradilan Tata Usaha Negara) merely regulates witnesses as a means of evidence and obligates their presence in court. From the perspective of Pancasila justice, justice refers to the balanced fulfillment of rights and obligations. Therefore, witnesses should not only bear obligations but also be granted rights (such as protection). The absence of witnesses in court has implications, such as being forcibly summoned by the police under the judge's order. While the state, through its instrument—the police—forces witnesses to attend court, it does not adequately consider how to protect them in the face of threats. Hence, in the future, witness protection in administrative court cases must be grounded in Pancasila justice and the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). Both serve as the foundation for the development of the national legal system.